The trouble with human capital theory - Blair Fix (Forum on Capital As Power - Toward a New Cosmology of Capitalism, 2018)
Human capital theory is the dominant approach for understanding personal income distribution. According to this theory, individual income is the result of "human capital". The idea is that human capital makes people more productive, which leads to higher income. But is this really the case? This paper takes a critical look at human capital theory and its explanation of personal income distribution. I find that human capital theory's claims are dubious at best. In most cases, the theory is either not supported by evidence, is so vague that it is untestable, or is based on circular reasoning. In short, human capital theory is a barrier to the scientific study of income distribution.
Keywords: 330; human capital theory; income distribution; critique; hierarchy; productivity; power